Repurposing FDA-Approved Agents to Develop a Prototype Helicobacter pylori Shikimate Kinase (HPSK) Inhibitor: A Computational Approach Using Virtual Screening, MM-GBSA Calculations, MD Simulations, and DFT Analysis - Abdulaziz H. Al Khzem; Tagyedeen H. Shoaib; Rua M. Mukhtar; Mansour S. Alturki; Mohamed S. Gomaa; Dania Hussein; Nada Tawfeeq; Mohsina Bano; Mohammad Sarafroz; Raghad Alzahrani; Hanin Alghamdi; Thankhoe A. Rants’o (Pharmaceuticals)
Background/Objectives: Helicobacter pylori infects approximately half of the global population, causing chronic gastritis, peptic ulcers, and gastric cancer, a leading cause of cancer mortality. While current therapies face challenges from rising antibiotic resistance, particularly to clarithromycin, alongside treatment complexity and costs, the World Health Organization has prioritized the development of new antibiotics to combat this high-risk pathogen. In this study, we employed computer-aided drug design (CADD) methodologies, including molecular docking, Molecular Mechanics-Generalized Born Surface Area (MM-GBSA) analysis, molecular dynamics (MD) simulations, and Density Functional Theory (DFT) calculations, to explore the potential repurposing of FDA-approved agents as inhibitors of Helicobacter pylori shikimate kinase (HpSK). Methods: Using the Glide module, the HTVS method was initially applied to screen 1615 FDA-approved agents followed by extra-precision (XP) docking for the obtained 111 hits. The obtained XP scores were used to confine the results to those hits with a score above the reference ligand, shikimate, score. This yielded 31 final hits with an XP score above −5.867. MM-GBSA calculations were performed on these top candidates and the reference ligand to refine the analysis and compounds’ prioritization. Results: The 31 compounds displayed binding free energy (ΔGbind) values ranging from 3.61 to −55.92 kcal/mol, with shikimate exhibiting a ΔGbind of −34.24 kcal/mol and 10 hits having a lower ΔGbind value. Out of these ten, three drugs—Dolutegravir, Cangrelor, and Isavuconazonium—were selected for further analysis based on their drug-like properties. Robust and stable binding profiles for both Isavuconazonium and Cangrelor were verified via molecular dynamics simulation. Additionally, Density Functional Theory (DFT) analysis was conducted, and the Highest Occupied Molecular Orbitals (HOMOs), Lowest Unoccupied Molecular Orbitals (LUMOs), and the energy gap (HLG) between them were calculated. All three drug candidates displayed lower HLG values than shikimate, suggesting higher reactivity and more efficient electronic transitions than the reference ligand. Conclusions: These findings suggest that the identified drugs, although not optimal for direct repurposing, would serve as promising leads against Helicobacter pylori shikimate kinase. These drugs could be valuable leads for experimental assessment and further optimization, particularly with no prototype yet identified. In terms of potential for clinical repurposing, the results point to diflunisal as a promising candidate for further testing.